IMPACT OF BRAND IMAGE ON BUYING BEHAVIOUR AMONG TEENAGERS - Ali Durrani, Baseer; Godil, Danish Iqbal; Baig, Mirza Uzair; Sajid, Sana (European Scientific Journal, ESJ, 2015)
The objective of this research study is to analyze the impact of brand image on teenagers brand choice, source of information, factors affecting buying choice and level of satisfaction. The sample of the study is 300 respondents in which 150 students were chosen from schools and 150 students were selected from colleges of Karachi. Two schools and two colleges were selected for this research study. Through a structured questionnaire data were collected and with the help of SPSS, analysis was made. The results revealed that values of regression analysis shows that there is 33.7% variance of buying behavior of teenagers explain by the impact of advertisement on buying behavior, advertisement’s impact on brand image and brand image impact on brand loyalty. The results of Pearson correlation shows that teenagers buying behavior is significantly 36% correlated with teenager’s loyalty and 49% with advertisement impact on brand image. The teenagers buying behavior is also 38.8% positively and significantly correlated with advertisement. The results of correlation also interpreting that the all relationship is positive and high significant at 0.01 level. There is a practical relation between brand image and consumer teenager buying behaviour. Marketers can utilize the findings in order to come up with carious marketing strategies in order to target teenagers in more precise manner.